Caracterização e viabilidade do uso de hidrogéis compósitos poli (álcoolvinílico)/atapulgita em sistemas de liberação de fármaco - Santana, Genelane Cruz (2012)
Composites hydrogels were developed in film shape based on poly vinyl alcohol (PVA) using acidified attapulgite as crosslinking agent. The hydrogel composites were obtained in solution with amounts of attapulgite ranging from 0.05 to 2% in the polymer matrix in order to study its influence on the crystallinity, in the swelling properties and in the release of gentamicin sulphate. The obtained composites were characterized by XRD, FTIR and DSC. According to XRD data the polymer crystallinity is not affected by the clay addition, however, the presence of attapulgite modifies the melting and crystallization temperatures, behavior observed by DSC measures. In general, graphical profile of FTIR showed that there are interactions between PVA and attapulgite. The hydration kinetics at 37°C is independent of pH values and shown to obey the Fickian diffusion mechanism with values of n<0.5. Thus, the viability of hydrogels in drug delivery systems was evaluated by the swelling degree and by in vitro release. These two aspects were dependent on the concentration of the drug. Thus, although preliminaries, the results from release of gentamicin sulphate using PVA/attapulgite composites hydrogels proved be promising for future application.